Milk Fat Globule-EGF Factor 8 Alleviates Pancreatic Fibrosis by Inhibiting ER Stress-Induced Chaperone-Mediated Autophagy in Mice - Ren, Yifan; Cui, Qing; Zhang, Jia; Liu, Wuming; Xu, Meng; Lv, Yi; Wu, Zheng; Zhang, Yuanyuan; Wu, Rongqian (Frontiers in Pharmacology, 2021)
Pancreatic fibrosis is an important pathophysiological feature of chronic pancreatitis (CP). Our recent study has shown that milk fat globule-EGF factor 8 (MFG-E8) is beneficial in acute pancreatitis. However, its role in CP remained unknown. To study this, CP was induced in male adult Mfge8-knockout (Mfge8-KO) mice and wild type (WT) mice by 6 intraperitoneal injections of cerulein (50 μg/kg/body weight) twice a week for 10 weeks. The results showed that knockout of mfge8 gene aggravated pancreatic fibrosis after repeated cerulein injection. In WT mice, pancreatic levels of MFG-E8 were reduced after induction of CP and administration of recombinant MFG-E8 alleviated cerulein-induced pancreatic fibrosis. The protective effect of MFG-E8 in CP was associated with reduced autophagy and oxidative stress. In human pancreatic stellate cells (PSCs), MFG-E8 inhibited TGF-β1-induced ER stress and autophagy. MFG-E8 downregulated the expression of lysosomal associated membrane protein 2A (LAMP2A), a key factor in ER stress-induced chaperone-mediated autophagy (CMA). QX77, an activator of CMA, eliminated the effects of MFG-E8 on TGF-β1-induced PSC activation. In conclusion, MFG-E8 appears to mitigate pancreatic fibrosis via inhibiting ER stress-induced chaperone-mediated autophagy. Recombinant MFG-E8 may be developed as a novel treatment for pancreatic fibrosis in CP.